Comparison of Mixed and Choice Feeding of Whole Wheat (Triticum aestivum) on the Performance of Commercial Broilers - Bhagora, Nikesh J; Savaliya, Fulabhai P; Patel, Atul B; Lonkar, Vijaysinh D (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Wheat is the cereal grain of choice for Whole Grain Feeding (WGF) in poultry, despite the fact that globally maize is the most commonly used cereal grain. In this context, in the present study feeding of whole wheat to commercial broilers with two types of feeding systems were used ie. mixed and choice feeding systems of wheat with different levels of replacement with maize by 20, 40, 60, 80 and 100%. The body weight and body weight gain of birds fed with 20% and 40% choice feeding of wheat was found to be the highest (p<0.05). The mean wheat consumption (g/bird) from total feed consumption under choice feeding during 2 to 6 weeks of age in birds fed with 20, 40, 60, 80 and 100% were found to be 363.18, 720.12, 1398.45, 2160.30 and 3202.10, respectively. Birds fed with choice feeding of 40% wheat showed significantly (p<0.05) improved FCR. The highest livability (%) was found in the birds fed with 40% and 100% choice feeding of wheat. The gizzard weight (g) showed non-significant difference among the birds fed with various treatment rations. The highest return over feed cost (in Rs.) was found in the birds fed with 40% choice feeding of wheat. The overall results indicated that choice feeding system is more suitable for better body weight gain and improved FCR as compared to mixed feeding system of whole wheat. Feeding with 40% maize in diet replaced by wheat and offered in separate feeder is more economical and profitable due to higher body weight gain, improved FCR and acceptable mortality.